Difficulty in Repurposing Selective Serotonin Reuptake Inhibitors and Other Antidepressants with Functional Inhibition of Acid Sphingomyelinase in COVID-19 Infection - Le Corre, Pascal; Loas, Gwenolé (Frontiers in Pharmacology, 2022)
COVID-19 has spread rapidly throughout the world becoming a health emergency so that drug treatments are urgently needed to control the outbreak especially in the more vulnerable individuals. This is reinforced by the fact that prophylactic vaccines and neutralizing monoclonal antibodies may not be fully effective against emerging variants. Despite all efforts made by the scientific community, efficient therapeutic options remain currently scarce, either in the initial as well as in the advanced forms of the disease. From retrospective observational studies and prospective clinical trials, selective serotonin reuptake inhibitors (SSRIs), and other antidepressants with functional inhibition of acid sphingomyelinase (FIASMAs), have emerged as potential treatment of COVID-19. This has led to some prematurely optimistic point of view, promoting a large prescription of fluvoxamine in patients with COVID-19, that we think should be reasonably tempered.